Information visualization for UM Library database / Sheena Mohd Arif - Sheena , Mohd Arif (2005)
This system is an enhanced prototype, called “Doc-with-Cone” to visualize information for University of Malaya Library (UML). The visualization concept adopted “Cam Tree” and “Cat-a-Cone” interfaces to perform a search on UML database. Focus of the project is to introduce an easier-to-use information retrieval system by embedding Human-Computer Interaction (HCI) features with stress on usability aspect in the prototype. The system development is also to help users retrieve more accurate results from the database in less time; compared using traditional OPAC system. The development is carried out based on System Development Life Cycle (SDLC) methodology with prototyping approach. The “Doc-with-Cone” is developed using Virtual Reality Modeling Language (VRML) and 3D Studio Max. It can be viewed via any web browser pre-installed with Cortona VRML Client plug-in. The proposed visualization works effectively on 3D plane for hierarchically structural information. Based on the assessment done with 20 participants at the end of the project, most users agree on positive aspects of usability factors and HCI features embedded in the prototype. Many of them see the prototype as a new positive concept to be introduced to Malaysian community in searching database.